2009
DOI: 10.1017/s1368980009991066
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis-oriented food patterns and incidence of hypertension: 6-year follow-up of the SUN (Seguimiento Universidad de Navarra) prospective cohort

Abstract: Objective: To study the association between adherence to several a priori-defined healthy food patterns and the risk of hypertension. Design: Prospective, multipurpose, dynamic cohort study (recruitment permanently open). We followed up 10 800 men and women (all of them university graduates), who were initially free of hypertension, for a variable period (range 2-6 years, median 4?6 years). During follow-up, 640 participants reported a new medical diagnosis of hypertension. Baseline diet was assessed using a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…A European cohort also found no dose-response relationship between diet score and hypertension, although the DASH score in that study was derived from only three food components (vegetables, fruits, and milk products) [11]. Another European cohort (SUN (Seguimiento Universidad deNavarra) prospective cohort) showed that higher adherence to DASH diet (assessed from six food components) was associated with lower risk of developing hypertension (P for trend ¼ 0.02) [12]. On the contrary, one study [12] showed some evidence that DASH diet influences longterm hypertension rates.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…A European cohort also found no dose-response relationship between diet score and hypertension, although the DASH score in that study was derived from only three food components (vegetables, fruits, and milk products) [11]. Another European cohort (SUN (Seguimiento Universidad deNavarra) prospective cohort) showed that higher adherence to DASH diet (assessed from six food components) was associated with lower risk of developing hypertension (P for trend ¼ 0.02) [12]. On the contrary, one study [12] showed some evidence that DASH diet influences longterm hypertension rates.…”
Section: Discussionmentioning
confidence: 93%
“…The relation of demographic variables or DASH score to BP change was estimated by using the coefficient of the cross product (interaction term) between these variables and time (years since exam 5 at the time of BP measurement). For potential confounders, we first adjusted for age (years) (model 1), then additionally adjusted for sex, smoking status (current, not current), alcohol intake (oz/week), history of diabetes (yes, no), BMI, and PAI (model 2) since these variables were considered to be associated with both diet intake and BP change, on the basis of the literature [10,12]. Furthermore, we conducted sensitivity analysis with additional adjustment for total energy intake, high-fat dairy intake, or both.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations